2022
DOI: 10.1002/adsc.202200586
|View full text |Cite
|
Sign up to set email alerts
|

One Pot Synthesis of 1,2‐Disubstituted Ethanones by Base‐Mediated Reductive Homocoupling of Aldehydes

Abstract: Reductive homocoupling transformations mediated by bases and TMSCN have been used as a strategy for synthesis of 1,2‐disubstituted ethanones. This protocol provides a method for synthesizing functionalized ethanones from aldehydes in one pot without transition metals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Very recently, we identified that bases can be effective accelerators in functionalization reactions involving carbonylation, deamination annulation, N -alkylation, transesterification, and cyclization . Based on these results and in combination with our interest in cross-coupling conversion and (de)­hydrogenation transformations to construct important scaffold molecules, we have developed a practical, direct, and effective method for the base-mediated tandem condensation N -alkylation of hydrazones and aldehydes with alkyl halides in tertiary butanol under mild conditions. Crucially, this synthetic scheme enables the preparation of a series of trisubstituted hydrazones in a one-pot reaction (Scheme , bottom).…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, we identified that bases can be effective accelerators in functionalization reactions involving carbonylation, deamination annulation, N -alkylation, transesterification, and cyclization . Based on these results and in combination with our interest in cross-coupling conversion and (de)­hydrogenation transformations to construct important scaffold molecules, we have developed a practical, direct, and effective method for the base-mediated tandem condensation N -alkylation of hydrazones and aldehydes with alkyl halides in tertiary butanol under mild conditions. Crucially, this synthetic scheme enables the preparation of a series of trisubstituted hydrazones in a one-pot reaction (Scheme , bottom).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with improvements in living standards, green and safe back-to-nature ways have become a pursuit for many people. A renewed international interest has arisen Nanomaterials 2022, 12, 3953 2 of 11 in natural dyes as they are among the promising options for developing a greener textile dyeing process [29,30]. Natural plant dyes applied to textile dyeing have been reported to confer a variety of health benefits and functionalities on textiles, such as UV protection, antibacterial activity, deodorization, anti-carcinogenicity, and anti-oxygenation [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%